Microbial Contamination of Mobile Phones Amongst Pharmacy Students in Gombe State University - Otegwu T. C.; Simi L. S; Obajuluwa A. F; Abdullahi F. B. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Mobile phones are becoming a necessary component of everyday life and are frequently taken into various places where they may harbor harmful bacteria. Studies have indicated that cell phones act as harbors for a variety of microbes. This investigation examined the bacterial contamination on phones of GSU’s Faculty of Pharmaceutical Sciences in Nigeria 200level pharmacy students. A random sample of one hundred (100) student mobile phones were utilized to collect demographic data and other pertinent data using a semi-structured questionnaire. The data indicates that 80% of students share their phones, 81% do not clean them every day, 73% use microfiber cloths, 13% wash their hands before using them, 11% use hand sanitizers before using them, and 24% use their phones while using the restroom. Standard microbiological techniques were used to analyze the samples, and isolates were obtained by swabbing them on differential agar surfaces. We isolated three different types of microorganisms: 63% gram-negative bacteria strains, 39% Staphylococcus aureus, and 1% Aspergillus niger. Antibiotics susceptibility testing conducted on the isolates obtained shows that majority of them are resistant to antibiotics. The findings also indicate that male students’ mobile phones have a higher level of contamination than those of female students.